Territorial perceptions of the impact of demographic dynamics. A study in the municipality of Capilla del Monte (Argentina) - Crissi Aloranti, Vanesa Soledad (2025)
Demographic growth driven by migratory flows influences territorial dynamics, reflecting socio-cultural and economic diversity. The aim of this article is to describe and make known the territorial perceptions of the community of Capilla del Monte about the demographic changes (population growth and new migration dynamics) in the last decade and their impact on planning processes. The study examines the challenges faced by the municipality in the face of disorderly population growth, real estate pressure in environmentally sensitive areas, and limited institutional capacity to update and enforce urban planning regulations. The methodological strategy adopted was a qualitative-quantitative triangulation at two points during 2024: first, structured surveys administered to 286 people over the age of 15, gauging perceptions of services, the environment, urban expansion, and current regulations; and second, participatory workshops with 284 secondary school students, using collective mapping techniques to identify socio-environmental issues from a neighbourhood perspective. The results highlight the preponderance of migrants in the locality and the social, cultural and institutional tensions that this generates. This scenario highlights the obstacles to sustainable territorial planning in a context of rapid urbanisation and limited regulatory control.